Use of emergency contraception and knowledge about its harms on Colombian female university students - Lina María Oliveros Riveros (Centro Provincial de Información de Ciencias Médicas, 2023)
Introduction: Sexual and reproductive education can prevent or reduce any physical or mental harm, or both, caused by risky sexual practices and inadequate use of contraceptive methods. Objective: To describe the use of emergency contraception among female university students and their awareness regarding the harms of these methods for their health. Methods: A descriptive and cross-sectional study was conducted, from April to October 2021, of 372 women over 18 years of age, enrolled in universities located in Medellin, Colombia, who were selected through non-probabilistic sampling. The information was obtained through a survey, which included variables related to the use of emergency contraception and the awareness of its harms. Results: In the case series, 67.7 % of the young women had used emergency contraceptives, with 8.7 % reporting using up to 3 levonorgestrel pills per month and 0.8 % using more than 10 in a year, while 97.8% considered that this type of method affected their health. Among the main adverse effects were irregular periods (65.8 %), nausea (31.7 %), vomiting (31.7 %), migraine (3.2 %) and mood changes (25.4 %). Conclusions: Although most of female university students who used emergency contraceptives were guided by medical recommendations, a small group did so inappropriately, which was associated with a low perception of the health harms of this method.